Pengembangan Media Pembelajaran Komik Elektronik untuk Pengenalan Keselamatan Kepada Anak Usia Dini - Suci Aprilyati Ruiyat (Departement of Mathematics Education, 2024)
This research is motivated by electronic comic learning media which features stories related to children's safety and security, making it a learning model that can be used by educators. With this, it is hoped that this electronic comic will become a learning innovation that can be used by Early Childhood educators to introduce and increase understanding related to the safety and security of Early Childhood. The aim of this research is to increase children's knowledge about safety talk. This research presents electronic comics that are easy to use and understood by young children so that children's understanding of their own safety increases. The type of method in this research is Research and Development (R&D) development with the ADDIE development model. Based on the data obtained, it shows that campaigning for health and safety in the school environment is an effort to prevent accidents and avoid undesirable things. Interesting methods and methods are needed to introduce safety talk to children so that children can carry out safety both for themselves and for others. Visual media is one thing that can be used to introduce children to the importance of safety. By using electronic comics, children can directly see the images presented in accordance with the prevention theme that will be conveyed. Children can directly choose the electronic comic story they want to know. By displaying attractive pictures and writing that is easy for children to understand, electronic comics are easy to understand.